Multiresidue Determination of Fluoroquinolones in Milk by Ion-Pair High Performance Liquid Chromatography - Lv, Yun-Kai; Qin, Li-Juan; Yu, Li-Qing; Sun, Han-Wen (Asian Journal of Chemistry, 2011)
A simple, sensitive and reliable ion-pair reverse phase high-performance liquid chromatography method has been developed and validated for the simultaneous determination of five fluoroquinolone residues in milk. The studied fluoroquinolones were ofloxacin, ciprofloxacin enrofloxacin, norfloxacin and sarafloxacin. Chromatographic separation was carried out on a Venusil XBP C18 column, in isocratic mode, with 0.025 mol/L H3PO4 solution, adjusted to pH 3.2 with 13 mmol/L tetrabutylammonium bromide-acetonitrile (96:4, v/v) as mobile phase. Good linearity over the investigated concentration range was observed, with mean values of correlation coefficients higher than 0.9993 for all the analytes studied. The limit of detection (LOD) and the limit of quantification (LOQ) with acceptable precision were 14.09, 46.97 mg/ kg for ofloxacin, 4.39, 14.64 mg/kg for norfloxacin, 10.18, 33.94 mg/kg for ciprofloxacin, 10.53, 35.12 mg/kg for enrofloxacin and 17.44, 58.14 mg/kg for sarafloxacin, respectively. These values are in compliance with requirements for monitoring of maximum residues levels. Overall recoveries from spiked milk samples ranged from 80.7 to 96.92 % with relative standard deviations lower than 4.23 %.